Exploring The Role of Halal Certification on Food Companies' Performance in Malaysia - Mohd Hashim Muda; Siti Zubaidah Muhammad; Alina Abdul Rahim; Norhayati Rafida Abdul Rahim; Sumaiyah Abd Aziz (Universiti Sains Islam Malaysia, 2024)
Non-Indexed Publication